2007
DOI: 10.4310/cms.2007.v5.n2.a10
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced stochastic resonance for Brownian ratchets under load

Abstract: Abstract. We consider a Brownian ratchet model where the particle on the ratchet is coupled to a cargo. We show that in a distinguished limit where the diffusion coefficient of the cargo is small, and the amplitude of thermal fluctuations is small, the system becomes completely coherent: the times at which the particle jumps across the teeth of the ratchet become deterministic. We also show that the dynamics of the ratchet-cargo system do not depend on the fine structure of the Brownian ratchet. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…They called this new phenomenon self-induced stochastic resonance (SISR); here, a weak noise amplitude could induce coherent oscillations (a limit cycle behavior) that the deterministic model equation cannot exhibit [1]. SISR has been investigated theoretically and numerical in different systems including Brown-ian ratchets and cancer model [40][41][42][43]. A natural question is: in what ways is SISR different from SR and CR?…”
Section: Introductionmentioning
confidence: 99%
“…They called this new phenomenon self-induced stochastic resonance (SISR); here, a weak noise amplitude could induce coherent oscillations (a limit cycle behavior) that the deterministic model equation cannot exhibit [1]. SISR has been investigated theoretically and numerical in different systems including Brown-ian ratchets and cancer model [40][41][42][43]. A natural question is: in what ways is SISR different from SR and CR?…”
Section: Introductionmentioning
confidence: 99%
“…However, with γ sufficiently large, it is reasonable to first average over the fast stochastic process and replace the detailed dynamics of the dX k equation with a model like that in Section 2 which encapsulates the jump times. The authors have performed a more detailed analysis of one example of such a system in DeVille and Vanden-Eijnden (2007) and shown that this scheme can be justified rigorously. Moreover, this analysis confirms that regularity and synchrony is not tied to a specific model but rather is quite generic to a wide class of systems where the Arrhenius timescale of jumping of the motors interplays in a nontrivial way with another slow timescale in the system.…”
Section: Outlook and Generalizationsmentioning
confidence: 94%
“…For example, Peskin and Elston gave theoretical evidence that motor cargo coupling is elastic [17]. Other more mathematical studies of Brownian particles explore topics such as stochastic resonance and coherence in molecular motors [18]. Similar results for flashing ratchets would be difficult to obtain using standard tools due to the hybrid nature of these systems.…”
Section: Introductionmentioning
confidence: 99%